CCNP Tshoot 642-832 quick reference - Stewart, Brent ([Cisco Press], 2010)
As a final exam preparation tool, the CCNP TSHOOT 642-832 Quick Reference provides a concise review of all objectives on the new CCNP TSHOOT exam (642-832). This eBook provides you with detailed, graphical-based information, highlighting only the key topics in cram-style format. With this document as your guide, you will review topics on maintaining networks, troubleshooting methodologies and tools, and troubleshooting practices for switches, routing, and security. This fact-filled Quick Reference allows you to get all-important information at a glance, helping you to focus your study on areas of weakness and to enhance memory retention of essential exam concepts.